Plant Vascular Cell Division Is Maintained by an Interaction between PXY and Ethylene Signalling - Etchells, J. Peter (Public Library of Science, 2012)
The procambium and cambium are meristematic tissues from which vascular tissue is derived. Vascular initials differentiate into phloem towards the outside of the stem and xylem towards the inside. A small peptide derived from CLV-3/ESR1-LIKE 41 (CLE41) is thought to promote cell divisions in vascular meristems by signalling through the PHLOEM INTERCALLATED WITH XYLEM (PXY) receptor kinase. pxy mutants, however, display only small reductions in vascular cell number, suggesting a mechanism exists that allows plants to compensate for the absence of PXY. Consistent with this idea, we identify a large number of genes specifically upregulated in pxy mutants, including several AP2/ERF transcription factors. These transcription factors are required for normal cell division in the cambium and procambium. These same transcription factors are also upregulated by ethylene and in ethylene-overproducing eto1 mutants. eto1 mutants also exhibit an increase in vascular cell division that is dependent upon the function of at least 2 of these ERF genes. Furthermore, blocking ethylene signalling using a variety of ethylene insensitive mutants such as ein2 enhances the cell division defect of pxy. Our results suggest that these factors define a novel pathway that acts in parallel to PXY/CLE41 to regulate cell division in developing vascular tissue. We propose a model whereby vascular cell division is regulated both by PXY signalling and ethylene/ERF signalling. Under normal circumstances, however, PXY signalling acts to repress the ethylene/ERF pathway.